Towards the construction of GSMN-based community model for an oral biofilm. Issue 26 (2019) - De Winter, Kjerstin; Ghesquière, Justien; Teughels, Wim; Waldherr, Steffen; Bernaerts, Kristel
Abstract: Oral biofilms form on all hard and soft surfaces of the oral cavity. When the microbial balance in this biofilm is disturbed, pathogens can take the overhand, and this can lead to periodontitis (i.e. a chronic and inflammatory disease of the gum and tooth supporting tissues). In this work, a dual species community model containing one commensal bacterium and the most common periopathogen, is presented. The commensal bacterium is Streptococcus gordonii, the periopathogen is Porphyromonas gingivalis. Existing Genome-Scale Metabolic Models (GSMNs) are curated and transformed into planktonic Dynamic Flux Balance Analysis (dFBA) models in DFBAlab (Gomez et al., 2014). In the planktonic model for S. gordonii, split ratio's are used to ensure correct flux distributions between the glycolysis and the pentose phosphate pathway and around the pyruvate node. The split ratios are required to simulate the suboptimal growth behaviour of this bacterium. Simulation results for the planktonic S. gordonii model are compared to experiments for pure cultures. The planktonic P. gingivalis model gives feasible results for biomass growth and nutrient uptake. Finally, both planktonic models are transformed into a biofilm model in DFBAlab by introduction of nutrient gradients over the depth of the biofilm. This first oral biofilm model predicted the partitioning of both bacteria in the biofilm, similar to what has been described in literature.